2017
DOI: 10.1155/2017/8085325
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Regulates the Bidirectional Differentiation of Bone Marrow Mesenchymal Stem Cells through Canonical Wnt Signaling Pathway

Abstract: Fat infiltration within the bone marrow is easily observed in some postmenopausal women. Those fats are mainly derived from bone marrow mesenchymal stem cells (BMMSCs). The increment of adipocytes derived from BMMSCs leads to decreased osteoblasts derived from BMMSCs, so the bidirectional differentiation of BMMSCs significantly contributes to osteoporosis. Icariin is the main extractive of Herba Epimedii which is widely used in traditional Chinese medicine. In this experiment, we investigated the effect of ica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…Icariin (ICA, C 33 H 40 O 15 , molecular weight: 676.67) is a natural flavonoid glycoside isolated from Herba Epimedii, which is used in traditional Chinese medicine for treatment of kidneys, joints, and other disorders . ICA has been shown to prevent ovariectomy (OVX)‐induced bone loss and it restored femoral strength in ovariectomized rats …”
Section: Introductionmentioning
confidence: 99%
“…Icariin (ICA, C 33 H 40 O 15 , molecular weight: 676.67) is a natural flavonoid glycoside isolated from Herba Epimedii, which is used in traditional Chinese medicine for treatment of kidneys, joints, and other disorders . ICA has been shown to prevent ovariectomy (OVX)‐induced bone loss and it restored femoral strength in ovariectomized rats …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the BMP2 and Runx2 increase was shown to be induced by Arneis PRPE, which is particularly rich in the flavonoid glycoside rutin. Flavonoid glycosides have been shown to possess a high osteogenic potential related to the stimulation of BMP2 and Runx2 expression (62)(63)(64)(65)(66)(67). More generally, polyphenols are able to enhance osteoblast activity and differentiation, by targeting Runx2 through different signaling pathways (16,50,(68)(69)(70) and by inducing the expression of bone-matrix related genes (71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that the small phytomolecule icaritin enhanced osteogenic differentiation of hBMScs in vitro, with the greatest effect demonstrated These results suggest that SOST is a key factor in the icaritin-mediated osteogenesis of hBMScs. Herba epimedii is used for curing bone-associated disorders in china (10). Icariin is considered to be the major pharmacologically active component and it promotes osteogenesis of hBMScs (10).…”
Section: Discussionmentioning
confidence: 99%
“…Icariin, extracted from Herba epimedii, has been suggested to significantly improve osteogenesis to decrease bone loss in ovariectomized rats and steroid-induced osteonecrosis of the femoral head (10). However, recent studies have demonstrated that icariin is enzymatically hydrolyzed, and then subsequently metabolized to desmethyl icaritin and icaritin; desmethyl icaritin is suggested to have more potent pharmacological effects compared with icariin (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation